Urban landscape, structural transformation and other development concerns in Iloilo City from the 19th century to the present - Madrid, Randy M. (Iloilo City UP Visayas, 2006)
"The paper highlighted Iloilo City's urban morphogenesis and demographic structural transformations as dictated by the changing environment and enterprise from the 19th century to the present. It attempted to draw the urban landscape of Iloilo from its beginning as an estuarine mangrove marsh to its transformation as a weaving town and a sugar entrepot of the country based on the analysis and interpretation of old photographs, sketches, historical records and notes, cadastral surveys, and planning blueprints. It also assessed the geo-political, socio-economic and historico-cultural patterns of development the city of Iloilo had undergone in relation to its changing landscape, physical structures and other urban concerns."
Keywords: Urbanization -- Iloilo City